Pengaruh Penerapan Model Pembelajaran Kooperatif Tipe Think Talk Write (TTW) Terhadap Kemampuan Komunikasi Matematis Peserta Didik Kelas VII SMPN 1 Pariaman Tahun Ajaran 2018/2019 - MAGFIRA ANNISA FITRI (Jurnal Edukasi dan Penelitian Matematika, 2019)
Mathematical communication skills are a basic abilities that must be possessed by students. However, in reality the mathematical communication skills of class VII students in SMP N 1 Pariaman are still low and learning process is still oriented towards teacher centered. The solution used to overcome thus problems are to use cooperative learning model; Think Talk Write (TTW). The type of the research is a quasy experiment with the design of Randomized Control-Grup Only Design.The sample in this research was two class choose is random. The instrument used to collect information in this research were final tests and quizzes. Analysis of the data used is the t test. Based on t test, can be concluded that studens who taught using the cooperative learning; Think Talk Write (TTW)  have better mathematical communication skills than students who taught using the direct learning model in class VII of SMP N 1 Pariaman.Keyword --- direct learning, mathematical communication skills, TTW learning model